Modeling the Effects of Standardized Ileal Digestible Tryptophan:Lysine Ratio on Growth Performance of 65- to 275-lb Pigs - M. A. Goncalves; M. D. Tokach; S. S. Dritz; K, J. Touchette; N. M. Bello; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
The objective of this study was to model the effects of standardized ileal digestible (SID) Trp:Lys ratio on growth performance of 65- to 275-lb pigs. The present experiment, along with three previous experiments from Gonçalves et al. (2014), were used in the analysis. For all studies, dietary treatments consisted of SID Trp:Lys ratios of 14.5, 16.5, 18.0, 19.5, 21.0, 22.5, and 24.5%. The experiments were 21 d in duration and used corn and soybean meal-based diets with 30% dried distillers grains with solubles formulated to be deficient in Lys at the end of each of the experiments. In the current experiment, a total of 975 gilts (337 × 1050; PIC, Hendersonville, TN) were used with initial BW of 234.1 ± 6.8 lb and final BW of 274.9 ± 10.4 (mean ± SD). Pens of pigs were blocked by weight and assigned to one of the seven dietary treatments in a randomized complete block design. There were 6 pens/treatment with 20 to 24 pigs per pen. For 235 to 275 lb-pigs, increasing SID Trp:Lys improved ADG (quadratic, P<0.022), ADFI (linear, P<0.001), and F/G (linear, P<0.001). Data from all experiments were then combined for analysis using linear and non-linear mixed models with random effects of experiment and weight block nested within experiment allowing for heterogeneous variances. Competing models included broken-line linear (BLL), broken-line quadratic (BLQ), and quadratic polynomial (QP). In the combined analysis for ADG, QP was the best fitting model and estimated SID Trp:Lys requirement at 23.5% (95% CI: [22.7, 24.3%]). In the combined analysis for F/G, BLL and BLQ had comparable fit and estimated SID Trp:Lys requirements at 16.9% (95% CI: [16.0, 17.8%]) and 17.0% (95% CI: [15.0, 18.9%]), respectively. Thus, the estimated mean requirements for SID Trp:Lys for 65- to 275-lb pigs ranged from 16.9% for optimum mean F/G to 23.5% for maximum mean ADG. Furthermore, 95% of the maximum estimated mean ADG was obtained by feeding 17.6% SID Trp:Lys and 98% of the maximum estimated mean ADG was obtained by feeding 19.8% SID Trp:Lys.
Keywords: amino acid ratio; growth; tryptophan; finishing pig